Manajemen Sumber Daya Manusia Berbasis Nilai Islam dalam Pengembangan Profesionalisme Guru - Abdussyukur, Abdussyukur; Fikri, Aiman; Nuraini, Nuraini; Karimah, Fakarotul; Patsun, Patsun; Gazali, Safril (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2026)
Human resource management (HRM) in education plays a strategic role in improving teacher professionalism as the main actor in the learning process. However, technocratic HRM practices often fail to deeply address ethical and value-based dimensions. This article aims to examine the role of Islamic values-based HRM in enhancing teacher professionalism through a literature review approach. The discussion focuses on integrating Islamic values such as trustworthiness (amanah), justice, responsibility, honesty, and sincerity into all stages of educational HRM, including planning, recruitment, competency development, performance appraisal, and career development systems. The findings indicate that Islamic values-based HRM contributes to the holistic development of teacher professionalism, encompassing not only pedagogical and professional competencies but also character building and professional ethics. Teachers are positioned not merely as professional workers, but as educators entrusted with moral and spiritual responsibilities. This approach also supports the creation of an educational work culture oriented toward quality, role modeling, and sustainability. Therefore, Islamic values-based HRM can serve as a relevant and contextual conceptual framework for strengthening teacher professionalism and improving the quality of Islamic educational institutions in response to contemporary educational challenges.ABSTRAKManajemen sumber daya manusia (SDM) dalam pendidikan memiliki peran strategis dalam meningkatkan profesionalisme guru sebagai aktor utama dalam proses pembelajaran. Namun, praktik manajemen SDM yang bersifat teknokratis sering kali belum menyentuh dimensi nilai dan etika secara mendalam. Artikel ini bertujuan untuk mengkaji peran manajemen SDM berbasis nilai Islam dalam meningkatkan profesionalisme guru melalui pendekatan kajian pustaka. Fokus pembahasan diarahkan pada integrasi nilai-nilai Islam seperti amanah, keadilan, tanggung jawab, kejujuran, dan keikhlasan dalam seluruh proses manajemen SDM pendidikan, mulai dari perencanaan, rekrutmen, pengembangan kompetensi, penilaian kinerja, hingga sistem penghargaan dan pembinaan karier guru. Hasil kajian menunjukkan bahwa penerapan manajemen SDM berbasis nilai Islam mampu membentuk profesionalisme guru secara holistik, tidak hanya pada aspek kompetensi pedagogik dan profesional, tetapi juga pada pembentukan karakter dan etika profesi. Guru diposisikan tidak sekadar sebagai tenaga kerja profesional, melainkan sebagai pendidik yang mengemban amanah moral dan spiritual. Pendekatan ini juga berkontribusi dalam menciptakan budaya kerja pendidikan yang berorientasi pada kualitas, keteladanan, dan keberlanjutan. Dengan demikian, manajemen SDM berbasis nilai Islam dapat dijadikan sebagai kerangka konseptual yang relevan dan kontekstual dalam upaya peningkatan profesionalisme guru serta penguatan mutu lembaga pendidikan Islam di tengah tantangan perubahan zaman.